PERAN GURU TERHADAP PENGEMBANGAN KARAKTER PERSPEKTIF TASAWUF - Roka'iyah, Sintia (IAIN Madura, 2021)
Education is important in today's era, including in the era of globalization which is growing rapidly. Education can shape a person into a quality person. One of the places to shape humans to have high quality and be able to develop the potential that exists in a person is education. In developing the character of students in schools, teachers have a strategic position as the main actor. The teacher is a figure who can be imitated or become an idol for students. Teachers can be a source of inspiration and motivation for their students. The attitude and behavior of a teacher is very imprinted on students, so that the speech, character and personality of the teacher become a mirror of students. Thus, teachers have a great responsibility in producing a generation of character, culture, and morality. the author uses qualitative research methods with the type of literature review. The library method is a data collection technique by conducting a review study of books, literatures, notes, and reports that have to do with the problems that are the object of research. Sufism is an activity of cleansing the soul, filling it with commendable qualities, and getting closer and in the presence of Allah. Sufism as mentioned in the meaning above, aims to obtain a direct and close relationship with God, directly without intermediaries.